Impact of Service Quality on Customer Loyalty: The Mediating Role of Customer Satisfaction in the Malaysian Telecommunication Sector - Devadas, Khamini; Kanapathy, Kanagi (Journal of Human Capital Development (JHCD), 2025)
This study examines the impact of service quality on customer loyalty in the Malaysian telecommunication sector, with the mediating role of customer satisfaction. The study measures service quality using the SERVQUAL dimensions, including tangibility, reliability, responsiveness, assurance, and empathy with two additional dimensions: network quality and convenience. The study collects the data through a structured survey from 362 telecom users across Malaysia. The findings of the study reveal that service quality significantly influence customer satisfaction, which in turn significantly mediates the relationship between service quality and customer loyalty. The study highlights the importance of enhancing both service delivery and network-related features to foster stronger customer relationships and sustained loyalty in a competitive telecom market in Malaysia.